The Impact of School Medicine on Population Health Formation - Muzashvili , Tea; Kazakhashvili, Nata (Caucasus Journal of Health Sciences and Public Health, 2020)
Each country plans its own health care system according to population quantity, age-sex structure, geographical differences, disease, genetics, as well as financial capabilities. One of the top priorities of the National Health Policy and Strategic Health Development Plan is disease prevention, population safety and health promotion. School medicine includes a variety of types of activities and opportunities to prevent disease, or to reduce the harmful effects of these factors. Many countries around the world consider school medicine as one of the least used resources for health promotion and disease prevention, so more and more attention has been paid to school medicine in recent times as a health care system priority. Scientific studies have confirmed the associations between the quality of health (physical, mental, personal development) and academic performance, which in turn allows the efficient use of the country’s financial resources. WHO’s initiative is important: The development of school medicine in line with global challenges, the relevance of this initiative has once again been confirmed by the COVID-19 pandemic in the world. The development of school medicine can have a great impact on the health of the population due to the following circumstances: 1) the large contingent of school students and the large human resources of the school teachers, as well as the administration; 2) Specificity and location of the school, environment 3) Close contact of schools with families, different segments of society, the community in general, as well as various agencies, provides a wide range of health care for the population. The goal of the WHO is to increase the number of «health support schools» by constantly strengthening its potential to create a healthy learning environment, work and life. The preventive direction of school medicine will contribute to the establishment of a healthy lifestyle, the upbringing of healthy future generations, the efficient spending of the country’s financial resources and the creation of a precondition for the well-being of citizens.